THE SUBJECT AND METHODS OF KNOWLEDGE OF ECONOMIC THEORY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
It is appropriate to start defining the subject of economic theory by studying and synthesizing various theoretical views.